2005
DOI: 10.1038/sj.leu.2403657
|View full text |Cite
|
Sign up to set email alerts
|

A new recurrent inversion, inv(7)(p15q34), leads to transcriptional activation of HOXA10 and HOXA11 in a subset of T-cell acute lymphoblastic leukemias

Abstract: Chromosomal translocations with breakpoints in T-cell receptor (TCR) genes are recurrent in T-cell malignancies. These translocations involve the TCRad gene (14q11), the TCRb gene (7q34) and to a lesser extent the TCRc gene at chromosomal band 7p14 and juxtapose T-cell oncogenes next to TCR regulatory sequences leading to deregulated expression of those oncogenes. Here, we describe a new recurrent chromosomal inversion of chromosome 7, inv(7)(p15q34), in a subset of patients with T-cell acute lymphoblastic leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 39 publications
0
81
2
1
Order By: Relevance
“…Gene expression analysis showed that the whole HOXA gene cluster was dramatically dysregulated in T-cell acute lymphocytic leukemia samples harboring the TCRb-HOXA rearrangement (Speleman et al, 2005;Cauwelier et al, 2007). HOXA genes were also found to be upregulated in MLL and CALM-AF10-related T-cell acute lymphoblastic leukemias cases, strongly suggesting that HOXA genes are oncogenic in these leukemias (Soulier et al, 2005).…”
Section: Deficiencies Of Hox Regulators Demonstrate a Role For Hox Gementioning
confidence: 99%
“…Gene expression analysis showed that the whole HOXA gene cluster was dramatically dysregulated in T-cell acute lymphocytic leukemia samples harboring the TCRb-HOXA rearrangement (Speleman et al, 2005;Cauwelier et al, 2007). HOXA genes were also found to be upregulated in MLL and CALM-AF10-related T-cell acute lymphoblastic leukemias cases, strongly suggesting that HOXA genes are oncogenic in these leukemias (Soulier et al, 2005).…”
Section: Deficiencies Of Hox Regulators Demonstrate a Role For Hox Gementioning
confidence: 99%
“…59 Chromosomal translocations also lead to ectopic expression of HOXA cluster genes by juxtaposition of TCRA regulatory elements with HOXA coding sequences in some patients with T-cell ALL. 60,61 In addition to these translocations, which directly lead to overexpression of HOX genes, a number of recent studies have demonstrated that chromosome translocations, which result in MLL fusions, lead to unscheduled expression of HOX genes in both AML and T-cell ALL patients. 62 In addition to these studies showing HOX gene dysregulation resulting from chromosomal translocations, global gene Role of CALM-AF10 gene fusion in acute leukemia D Caudell and PD Aplan expression profiling has identified HOX genes as being consistently overexpressed in AML.…”
Section: Role Of Calm-af10 Gene Fusion In Acute Leukemia D Caudell Anmentioning
confidence: 99%
“…However, we may also not forget that cryptic chromosomal translocations and inversions could also still be undiscovered, as was illustrated by the recent identification of a cryptic t(9;14) resulting in an EML1-ABL1 fusion in T-ALL, 38 and a cryptic inv(7) affecting the HOXA cluster in T-ALL. 39 Finally, point mutations and other subtle nucleotide changes can only be identified by sequencing analysis. Large-scale sequence analysis of all kinase genes has already resulted in the identification of novel tyrosine kinase mutations, including ERBB2 in lung cancer and JAK2 in CMPDs.…”
Section: Kit D816v Mutation In Smmentioning
confidence: 99%